The effect of selective internal radiation therapy with yttrium-90 resin microspheres on lung carbon monoxide diffusion capacity - CEYHAN, BERRİN; BALTACIOĞLU, FEYYAZ; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (SPRINGER, 2017)
Background: Selective internal radiation therapy (SIRT) with embolization of branches of the hepatic artery is a valuable therapeutic tool for patients with hepatic malignancies; however, it is also associated with lung injury risk due to shunting. Diffusion capacity of the lungs for carbon monoxide (DLCO) is a clinically significant lung function test, and worsening in DLCO is suggested to reflect a limited gas exchange reserve caused by the potential toxicity of chemoradiotherapy or it may be a marker of related lung injury. This study aimed to examine the changes in DLCO during SIRT with resin microspheres in newly treated and retreated patients. Forty consecutive patients who received SIRT for a variety of malignant conditions were included. All subjects were treated with Yttrium-90 labelled resin microspheres. DLCO tests were performed after the procedures. In addition, patients were specifically followed for radiation pneumonitis. Results: The mean DLCO did not significantly change after the first (82.8 +/- 19.4 vs. 83.1 +/- 20.9, p = 0.921) and the second treatments (87.4 +/- 19.7 vs. 88.6 +/- 23.2, p = 0.256). Proportion of patients with impaired DLCO at baseline was not altered significantly after the first (37.5 vs. 45.0%, p = 0.581) and the second treatments (27.3 vs. 27.3%, p = 1.000). Also, percent change in DLCO values did not correlate with radiation dose, lung shunt fraction, or lung exposure dose (p > 0.05 for all comparisons). None of the patients developed radiation pneumonitis. Conclusions: Our results suggest that no significant change in DLCO in association with SIRT occurs, both after the first or the second treatment sessions. Further larger studies possibly with different protocols are warranted to better delineate DLCO changes after SIRT in a larger spectrum of patients.
Keywords: Selective internal radiation therapy (SIRT); Lung carbon monoxide diffusion capacity (DLCO); Radiation pneumonitis; NORMAL ORGAN WEIGHTS; II-THE-BRAIN; MAA SCINTIGRAPHY; SHUNT FRACTION; TC-99M MAA; PNEUMONITIS; RADIOEMBOLIZATION; LIVER; CANCER; BRACHYTHERAPY